ANALISIS SINYAL GETARAN DALAM DOMAIN FREKUENSI PADA MESIN BERPUTAR MENGGUNAKAN METODE FAILURE ANALYSIS - Ariesa Prisilia Yustin; Fajar Aswin; Angga Sateria (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
This research emphasized on failure analysis method that used in the process of analyzing 3 failures such as unbalance, bearing defect, and mechanical looseness based on domain frequency of vibration signal. Diagnosing failures by vibration signal that obtain by specific frequency that is showing the failure or defect followed by analyzing using failure analysis method. The final result that obtained after experiment is failure analysis method can determine one failure mode in each data that has been taken. Unbalance failure that indicated because of the highest peak of amplitude is appear on 1x rpm (31,25 Hz), bearing defect amplitude peak on 1x BSF frequency (49,82 Hz), and mechanical looseness on 0,5x, 1x, 2x, 3x rpm.